Streptococcus pneumoniae carriage studies in adults - Miellet, Willem R. (2023)
Funding Information: The authors declare that this study received funding from GlaxoSmithKline Biologicals SA. The funder was not involved in the study design, collection, analysis, interpretation of data, the writing of this article, or the decision to submit it for publication. Funding for this study was provided in part (SA and RS-L) by LISBOA-01-0145-FEDER (Microbiologia Molecular, Estrutural e Celular, funded by FEDER through COMPETE2020 – Programa Operacional Competitividade e Internacionalização), the authors received no other form of compensation or financial support related to the development of the manuscript. Funding Information: KT reports receiving consultation and speaking fees and funds for unrestricted research grants from Pfizer, and funds for unrestricted research grants and consultation fees from Merck Sharp & Dohme, all paid directly to his home institution and none related to the present work. RS-L reports receiving consultation and speaking fees from Pfizer and consulting fees from Merck (US). RS-L reports also receiving funds for unrestricted research grants from Pfizer and Merck Sharp & Dohme not related to the present work, paid directly to her home institution. Publisher Copyright: Copyright © 2023 Miellet, Almeida, Trzciński and Sá-Leão.